TIME ACCELERATION ANALYSIS AND OPTIMAL COST OF HOSPITAL HOSPITAL DEVELOPMENT PROJECT ON SHIP BUILDING USING CRITICAL PATH METHOD (CASE STUDY: PT. PAL INDONESIA (PERSERO)) - Agung Tresnadi; Suparno Suparno; Sutrisno Sutrisno; Wawan Kusdiana (JOURNAL ASRO, 2021)
Hospital Auxiliary Ship is an Indonesian Navy ship produced by PT. PAL Indonesia (Persero). The construction of this BRS ship was very time consuming and one of the main parts of the ship building project was the construction of the hull structure. In relation to time and production costs, the shipyard must be as efficient as possible in the use of time in each activity or activity, so that costs can be minimized from the original plan. Acceleration of the total duration in a project is done by accelerating critical activities in the project. To find out which are the critical activities of a project, the Critical Path Method (CPM) technique is used; namely by drawing a Network Diagram of the project. By using the CPM method in scheduling a ship hull construction project, it can be seen which activities should take precedence so as not to experience delays and waste. After that, the crashing method is carried out by increasing work hours (overtime) which aims to speed up the time of the project. The results of research for activities that are in the initial critical path with the CPM method can be seen as activities A, C, H, M, R, W, AB, AC, AD, AI, AP, AT, BA, BJ, BN. After accelerating, the critical path activities include activities A, C, H, M, R, W, X, AC, AD, AI, AP, AT, BA, BH, BO. Calculation of the project during initial conditions with Early working days without using overtime hours PT PAL Indonesia (Persero) costs Rp. 5,299,631,000, - while the Crashing Method is through the addition of 1 hour / day overtime so that the project implementation can be accelerated from the initial implementation of 450 days to 412 days and PT. PAL Indonesia (Persero) issued a project cost of Rp. 5,323,752,480, -. Keywords: Hospital Support Ship, Scheduling, CPM, Crashing.